A determining influence for CpG dinucleotides on nucleosome positioning in vitro - Davey, Colin S. (Oxford University Press, 2004)
DNA sequence information that directs the translational positioning of nucleosomes can be attenuated by cytosine methylation when a short run of CpG dinucleotides is located close to the dyad axis of the nucleosome. Here, we show that point mutations introduced to re-pattern methylation at the (CpG)(3) element in the chicken β(A)-globin promoter sequence themselves strongly influenced nucleosome formation in reconstituted chromatin. The disruptive effect of cytosine methylation on nucleosome formation was found to be determined by the sequence context of CpG dinucleotides, not just their location in the positioning sequence. Additional mutations indicated that methylation can also promote the occupation of certain nucleosome positions. DNase I analysis demonstrated that these genetic and epigenetic modifications altered the structural characteristics of the (CpG)(3) element. Our findings support a proposal that the intrinsic structural properties of the DNA at the −1.5 site, as occupied by (CpG)(3) in the nucleosome studied, can be decisive for nucleosome formation and stability, and that changes in anisotropic DNA bending or flexibility at this site explain why nucleosome positioning can be exquisitely sensitive to genetic and epigenetic modification of the DNA sequence.